Application of choice experiment method in protected area: a bibliometric analysis - Nor Hizami, Hassin; Kamaludin, Mahirah; Abd Aziz, Azlina; Mat Alipiah, Roseliza (Universiti Malaysia Terengganu, 2024)
Research on the application if the Choice Experiment (CE) method in protected areas has garnered increasing attention as a result of its efficacy in understanding complex socio-economic factors influencing conservation decision-making. However, a comprehensive and thorough analysis of the research landscape in this field has been scarce. This research aims to address the gap by conducting a bibliometric analysis to explore trends, key contributors, and thematic focuses in applying the CE method in protected areas. Using Scopus Analyser and VOSviewer software, data was analysed to answer seven research questions: (1) research trends in the CE method as per the publication year, (2) type of documents by the subject of research, (3) top 10 authors as per the citation by research, (4) map of co-authorship about the CE method application, (5) popular keywords associated to the research, (6) co-authorship countries’ collaboration, and (7) network mapping based on citation by source type. Results revealed central figures in collaborative networks, key thematic areas, international collaboration patterns, and influential scholarly outlets. The findings highlight interdisciplinary research, an emphasis on collaboration, and advocate methodological advancements to tackle conservation challenges. It offers compelling evidence of the increasing significance and multidisciplinary character of research employing the CE method in protected areas. This study also contributes to a comprehensive understanding of socio-economic aspects in conservation and management, aiding in evidence-based policy-making and fostering sustainable conservation practices globally.